Consider mission in decisions about pricing, aid strategy. Issue 6 (22nd January 2018) - Hope, Joan
Abstract : A few years ago, officials at Blackburn College in Illinois hired an enrollment consultant to help them recruit students. But the strategy failed, and the freshman class shrank.